Manajemen Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan di SMP Berbasis Pesantren - Sajidin Sajidin; Romi Siswanto (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2020)
This article aims to 1) To find out how the process of implementing principal management in increasing educational quality at SMP BP Amanatul Ummah. 2) Knowing what are the supporting and inhibiting factors of the principal management process in improving the quality of education at SMP BP Amanatul Ummah. 3) Knowing the principal management process on the quality of professional education at SMP BP Amanatul Ummah Pacet Mojokerto. This research is qualitative research using descriptive methods, namely research methods to solve actual problems. Data collection was carried out through observation, interviews, and documentation. The management of school principals in order to increase education output at SMP BP Amanatul Ummah the program carried out is to increase the ability of school personnel in resource management and program preparation, encouraging greater community participation to support education in schools, encouraging the use of school budgets according to school needs. functions are implemented by taking four stages, namely: planning, organizing, implementing and supervising. From the results of research and data obtained from the implementation of school principal management, the impact of the implementation of BP Amanatul Ummah Junior High School education, especially the achievement of students, shows high achievement both academic and non-academic achievements. In implementing principal management, it is inseparable from supporting and inhibiting factors, to anticipate inhibiting factors a solution is needed to overcome them.